2004
DOI: 10.1111/j.1601-5223.2001.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential FISH Analysis with rDNA Genes and Ag-NOR Banding in the Lady Beetle Olla v-nigrum (Coleoptera: Coccinellidae)

Abstract: We have characterized the meiosis of Olla v-nigrum by standard analysis, performed a NOR study using NOR banding, FISH of rDNA genes and sequential FISH/AgNOR analysis, and adapted the FISH methodology to Coccinellidae. The chromosome number determined at metaphase I was n = 9 + Xyp. At zygotene it was possible to identify the sex vesicle which presented a deeply stained heteropycnotic block. Chromosome X is much larger than the y and the two combine, forming a "parachute" in metaphase I. FISH analysis using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Another small DA/CMA 3 + band seen with or without the C banding treatment which presented the shape and richness in GC base pairs led us to believe that we were evidencing a nucleolar organizer region (NOR) (Figure 3 arrowhead). This correlation between CMA 3 + bands and NORs is quite common among animals and in insects has been observed in: the grasshoppers Eyprepocnemis plorans and Locusta migratoria (Camacho, et al, 1991); the wasp Trypoxylon albitarse (Araújo et al, 2000;2002); the lady beetle Olla v-nigrum (Maffei et al, 2001a); and in other Meliponini bees such as Melipona (Rocha and Pompolo, 1998;Rocha et al, 2002); Plebeia (Caixeiro, 1999) and Friesella 54 Brito et al schrottkyi (Mampumbu, 2002). The location of these regions by the classical technique of Howell and Black (1980) is difficult on Meliponinae chromosomes that was effectively achieved only in Tetragonisca angustula (Menezes, 1997), Melipona (Maffei et al, 2001b;Rocha et al, 2002); Plebeia (Maffei et al, 2001b) and Friesella schrottkyi (Mampumbu, 2002).…”
Section: Resultsmentioning
confidence: 70%
“…Another small DA/CMA 3 + band seen with or without the C banding treatment which presented the shape and richness in GC base pairs led us to believe that we were evidencing a nucleolar organizer region (NOR) (Figure 3 arrowhead). This correlation between CMA 3 + bands and NORs is quite common among animals and in insects has been observed in: the grasshoppers Eyprepocnemis plorans and Locusta migratoria (Camacho, et al, 1991); the wasp Trypoxylon albitarse (Araújo et al, 2000;2002); the lady beetle Olla v-nigrum (Maffei et al, 2001a); and in other Meliponini bees such as Melipona (Rocha and Pompolo, 1998;Rocha et al, 2002); Plebeia (Caixeiro, 1999) and Friesella 54 Brito et al schrottkyi (Mampumbu, 2002). The location of these regions by the classical technique of Howell and Black (1980) is difficult on Meliponinae chromosomes that was effectively achieved only in Tetragonisca angustula (Menezes, 1997), Melipona (Maffei et al, 2001b;Rocha et al, 2002); Plebeia (Maffei et al, 2001b) and Friesella schrottkyi (Mampumbu, 2002).…”
Section: Resultsmentioning
confidence: 70%
“…The FISH results with rDNA 18S probe confirmed that pairs number 2, 9, 10 and 15 carry cistrons for the ribosomal RNA. The same correspondence of CMA 3 ϩ /NOR has been observed in the coleopteran Olla v-nigrum (Maffei et al 2001a); and in the wasp Trypoxylon albitarse (Araújo et al 2000); the stingless bees Plebeia and Melipona (Maffei et al 2001b); Friesella schrottkyi (Mampumbu 2002) and Partamona peckolti (Brito et al 2003).…”
Section: Number and Localization Of Nor Sites By Fishmentioning
confidence: 56%
“…In T. chanchamayoensis, a marked reaction was seen with DA/CMA 3 ( Figure 4A), while in T. recursa, the staining with CMA 3 revealed no GC-rich regions in the chromosomes ( Figure 4B). The positive reactions seen were probably associated with nucleolus organizing regions (NORs), as observed in 188 Costa et al other insects such as Orthoptera (Camacho et al, 1991), Coleoptera (Maffei et al, 2001), and in other Hymenoptera, including Formicidae (Palomeque et al, 1988;Imai et al, 1992), Sphecidae (Araújo et al, 2000) and Meliponini (Brito et al, 1999(Brito et al, , 2003Caixeiro, 1999;Rocha, 2000). Some authors have suggested that the number of NORs revealed by impregnation with silver nitrate or by CMA 3 staining is an important taxonomic character.…”
Section: Resultsmentioning
confidence: 99%